Zero-carbon homes : a road-map - Williams, Jo (Joanna) (Abingdon, Oxon ; Earthscan, 2012)
'Housing is a major contributor to CO2 emissions in Europe and America today and the construction of new homes offers an opportunity to address this issue. Providing homes that achieve'zero carbon','carbon neutral','zero-net energy' or'energy-plus' standard is becoming the goal of more innovative house-builders globally, whilst energy providers seek to decarbonise the energy supply to new and existing development. Various new technical systems for achieving these goals are beginning to emerge. For example the passive house whose energy requirement for space heating and cooling is almost zero; the smart grid that has revolutionised the management of energy, whilst enabling the connection of small-scale, renewable energy producers and electric vehicles to the grid; or the European super-grid which will enable zero carbon energy to be generated in the Sahara desert and stored in Norway. This book explores the diverse approaches that are being adopted around the world to delivering zero carbon homes and the different societal systems and geographic circumstances in which they have developed. It postulates a roadmap for delivering zero carbon homes, together with a toolbox approach for policy and practice to suit particular national and local circumstances.A series of case studies are presented that offer lessons for delivering zero carbon homes. These examples are also used to demonstrate how prototype systems can move into the mainstream. The book highlights some of the instruments and mechanisms that could be used to support this transformation and addresses the wider implications of introducing these innovative systems in terms of industry, lifestyle and urban form.'--
'Housing is a major contributor to CO2 emissions in Europe and America today and the construction of new homes offers an opportunity to address this issue. Providing homes that achieve'zero carbon','carbon neutral','zero-net energy' or'energy-plus' standard is becoming the goal of more innovative house-builders globally, whilst energy providers seek to decarbonise the energy supply to new and existing development. Various new technical systems for achieving these goals are beginning to emerge. For example the passive house whose energy requirement for space heating and cooling is almost zero; the smart grid that has revolutionised the management of energy, whilst enabling the connection of small-scale, renewable energy producers and electric vehicles to the grid; or the European super-grid which will enable zero carbon energy to be generated in the Sahara desert and stored in Norway. This book explores the diverse approaches that are being adopted around the world to delivering zero carbon homes and the different societal systems and geographic circumstances in which they have developed. It postulates a roadmap for delivering zero carbon homes, together with a toolbox approach for policy and practice to suit particular national and local circumstances. A series of case studies are presented that offer lessons for delivering zero carbon homes. These examples are also used to demonstrate how prototype systems can move into the mainstream. The book highlights some of the instruments and mechanisms that could be used to support this transformation and addresses the wider implications of introducing these innovative systems in terms of industry, lifestyle and urban form'--
Machine generated contents note: 1.Introduction -- PART 1 -- 2.Zero carbon homes: the technological response -- PART 2 -- 3.Innovative housing programmes -- 4.Low/zero carbon energy systems -- 5.Low/zero carbon neighbourhoods -- PART 3 -- 6.Markets for zero carbon homes -- 7.Transformation of the house-building industry -- 8.Transformation of the energy industry -- 9.Instruments for change -- 10.A spatial dimension -- 11.Living with zero carbon -- 12.A time for change.
Includes bibliographical references and index.
Keywords: Ecological houses; Carbon dioxide mitigation